Profile of methods in suicide attempts: Trends and implications for prevention. Jujuy, northwestern of Argentina - López Steinmetz, Lorena Cecilia (2019)
This article reports the first description of the methods profile in suicide attempts conducted up to date in Jujuy (Argentina), and a discussion of its implications for prevention. The study was epidemiological and transversal. Data set include all suicide attempts (n = 481) psychologically assisted during two biennia at the Emergency Service of the main hospital. Using a single method was prevalent (84%) in all age ranges and in both sexes, but combining methods it is characterized by males (p< .05). Self-poisoning by medications (39.8%) and self-harm by cuts (27.3%) were the most frequent in both sexes. Non-violent methods were prevalent in both sexes, although males tended to use more violent and potentially more lethal methods. Some of the identified methods might be prevented simply by limiting their availability (e.g., medications, especially psychotropic, alcoholic beverages, jumping sites, firearms). Instead, other methods (e.g., hanging, gases, cleaning products, etc.) are difficult to be restricted.